The logic of anarchy neorealism to structural realism - Buzan, Barry; Jones, Charles A.; Little, Richard (New directions in world politics, 1993)
This treatise attempts to release structural theory from the confines of neorealism, and in the process lays the groundwork for a comprehensive theory of international relations based upon a methodologically open structural realism.